The Essence of Creativity, its Place and Role in Human Activity - Abdurakhimovna, Bozorboeva Zuhra (European Journal of Life Safety and Stability (2660-9630), 2022)
To understand the essence of creativity, it is important to understand its nature, dynamics as a process, genesis of results, their relationship to reality. Creativity in its first definition is manifested as human activity that creates new spiritual and material values. The artificial environment surrounding the human being - "second nature" is a product of creativity in its diversity, enormous production forces, spiritual values, culture - in terms of quality.